(3GdCQHYhf MOjKG aj LhGeY Gdcde GdbOSjIs - (3GdgQhj, GdbGQj, CHh GdMSf, fhQ GdOjf (B- (3GdeqdG, Ydj Hf (B((3SdWGf(B) (3eMeO, (B1014 (3g`s ((3HQhSg (B( (3cRjOg (B)s)
(3ChdgG (B:s
(3HYO GdHSedI ; eaJGM cd cJGH cQje ceG QhGg GdNWjH aj GdLGeY Yf GdQShd GdYXje GdMeO ddg GdPj GhLO GdNdb ef GdYOe hHYO agPg CQHYhf MOjKG eHGfjgG jSjQI LeYgG Ydj Hf SdWGf eMeO GdbGQj s
(3BNQgG (B:s
(3hbO QhGg GdMSf Yf GdMSf Yf CHj GdMSf Yf LO GdMSf (B" (3Cf CMSf GdMSf GdNdb GdMSf(B" (3ceG CNQLg TjN eTGjNfG GdLdGd GdSjhWj hgh MOjK MSf hESfGOg MSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 12s
(3eYLe GdeDdajf (B2 / 446s
(3cTa GdXfhf (B1/ 61s
(3gOjI GdYGQajf (B1 / 751s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs